Promoting smart travel through tax policy - Pearce, Prafula; Hodgson, Helen (Taxation Institue of Australia, 2015)
This article discusses the need for the Australian Government to explore smart commuting policies due to the impact of using passenger motor vehicles on negative transport externalities, such as congestion, greenhouse gas emissions, health and safety, energy security and economic prosperity. The lack of tax incentives and the convenience of parking facilities provided by employers are barriers to the adoption of travel smart choices. This article explores the tax constraints that hinder smart commuting and examines how a subsidy for smart commuting can be provided through tax policy changes, especially the fringe benefits tax. In the authors’ opinion, the Australian Government should follow the example of other countries that are using taxation as a tool to promote alternative travelling initiatives, such as the transit program in the United States, the Cycle to Work Alliance in the United Kingdom, and the income tax exemption in Ireland.